2013
DOI: 10.1002/ggge.20111
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical insight into differences in the physical structures and dynamics of two adjacent maar lakes at Mt. Vulture volcano (southern Italy)

Abstract: [1] We report on the first geochemical investigation of the Monticchio maar lakes (Mt. Vulture volcano, southern Italy) covering an annual cycle that aimed at understanding the characteristic features of the physical structures and dynamics of the two lakes. We provide the first detailed description of the lakes based on high-resolution conductivity-temperature-depth (CTD) profiles, chemical and isotopic (H and O) compositions of the water, and the amounts of dissolved gases (e.g., He, Ar, CH 4 , and CO 2 ). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…Similar 3 He/ 4 He values, measured in fluids from around Mt. Vulture, indicate that the deep volcanic system is still degassing (Caracausi et al, 2009(Caracausi et al, , 2013bChiodini et al, 2000a). The two maar lakes act as collectors of mantle-derived He and CO 2 (Caracausi et al, 2013b and references therein) and in the last few centuries they have shown evidence of several sudden releases of mantle-derived fluids, which had accumulated in the crust and/or volatiles which had outgassed from magma (Caracausi et al, 2009 and references therein).…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…Similar 3 He/ 4 He values, measured in fluids from around Mt. Vulture, indicate that the deep volcanic system is still degassing (Caracausi et al, 2009(Caracausi et al, , 2013bChiodini et al, 2000a). The two maar lakes act as collectors of mantle-derived He and CO 2 (Caracausi et al, 2013b and references therein) and in the last few centuries they have shown evidence of several sudden releases of mantle-derived fluids, which had accumulated in the crust and/or volatiles which had outgassed from magma (Caracausi et al, 2009 and references therein).…”
Section: Introductionsupporting
confidence: 68%
“…Hence geochemical evidences support that an active outgassing of mantlederived volatiles from magmatic intrusion at depth occurs in the region of the Mt. Vulture volcano (Caracausi et al, 2013a(Caracausi et al, , 2013b. This is strongly supported by recent geophysical investigations that highlighted: 1) the presence of magmatic intrusions between 5 and 20 km at depth under the Mt.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations